Pamali Banjar dan Ajaran Islam - Dede Hidayatullah (Balai Bahasa Sulawesi Tengah, 2019)
Islam and Banjar people are one in unity. Banjar people also know and use the pamali in their daily lives. On the other hand, pamali is considered by the Banjar people as pamali. The objective of this study is to describe pamali originating from Islamic teachings such as the Qur'an and hadith. The results of this study prove that the Banjar pamali is partly derived from the Qur'an, and hadith, and the words of the ulama. The pamali from the teachings of Islam and the five pillars of Islam is in the way of eating and drinking, sleeping, farming.